Relevansi Hermeneutika Schleiermacher dalam Interpretasi Novel Perempuan di Titik Nol Karya Nawal El Saadawi (Al-Mashadir: Journal of Quranic Sciences and Tafsir, 2025)
This writing discusses the thoughts of Schleiermacher and the application of his hermeneutical theory. Hermeneutics, which has been studied for a long time, has recently become an interesting topic to discuss in philosophical studies. In the classical view, hermeneutics reminds us that the words we speak are symbols of our mental experiences, and the words we write are symbols of what we speak. If someone does not share the same written language with others, they will also not share the same spoken language. Hermeneutics, as the science of interpretation, first emerged in the seventeenth century with two meanings: as a set of methodological principles for interpreting texts and as a philosophical inquiry into the nature and inevitable conditions in the process of understanding. One hermeneutics figure, Schleiermacher, was a theologian and philosopher from Germany. He brought the theory of hermeneutics from Biblical studies into the realm of philosophy, so that now all forms of texts can become objects to be interpreted. Therefore, Schleiermacher is considered a philosopher who revived hermeneutics and made it a method of interpretation that applies not only to religious texts but also to art, literature, and history. Likewise, in this article, which examines the novel Woman at Point Zero using Schleiermacher's hermeneutic theory. A phenomenal and very famous novel in Egypt, written by Nawal El Saadawi based on the experiences of women she encountered in Qanatir Prison, Egypt. There are several points of applying Schleiermacher's hermeneutics in this novel, namely in the social and cultural context, empathy towards the author and characters, language and symbols, as well as the reader's interpretation.